2006
DOI: 10.1016/j.drugalcdep.2006.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Drug and alcohol-impaired driving among electronic music dance event attendees

Abstract: Background-Drug-impaired driving has received increased attention resulting from development of rapid drug-screening procedures used by police and state laws establishing per se limits for drug levels in drivers. Venues that host electronic music dance events (EMDEs) provide a unique opportunity to assess drug-impaired driving among a high proportion of young adult drug users. EMDEs are late-night dance parties marked by a substantial number of young adult attendees and elevated drug involvement. No studies to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 14 publications
4
39
0
2
Order By: Relevance
“…As the night passes, students reported more frequent use of cocaine, ecstasy, and LSD. Multiple drug use, as found in the present study, has been reported for the population, in particular for the young adults (Furr-Holden et al, 2006;Midanik et al, 2007), which leads to an increased effect on psychomotor performance, as well as an increase in traffic accident risk (Laumon et al, 2005;Ramaekers et al, 2004Ramaekers et al, , 2006Richer and Bergeron, 2009). It should be mentioned that, in the present study, no information was recorded regarding exposure in terms of kilometres driven.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…As the night passes, students reported more frequent use of cocaine, ecstasy, and LSD. Multiple drug use, as found in the present study, has been reported for the population, in particular for the young adults (Furr-Holden et al, 2006;Midanik et al, 2007), which leads to an increased effect on psychomotor performance, as well as an increase in traffic accident risk (Laumon et al, 2005;Ramaekers et al, 2004Ramaekers et al, , 2006Richer and Bergeron, 2009). It should be mentioned that, in the present study, no information was recorded regarding exposure in terms of kilometres driven.…”
Section: Discussionsupporting
confidence: 76%
“…Driving after alcohol and drug use was also previously reported in the adult population (1.9%, Walsh and Mann, 1999, and 1.5%, Alvarez et al, 2007), regular cannabis users (82%, Terry andWright, 2005, and78%, Jones et al, 2007), and young adults attending electronic music dance events (61.8%, Furr-Holden et al, 2006).…”
Section: Discussionsupporting
confidence: 59%
“…46 Lyrics of some music genres, such as rock, heavy metal, rap, and new emerging genres such as reggaeton, have been found to revolve around topics such as sexual promiscuity, death, homicide, suicide, and substance abuse. 9,13,17,43,45,[46][47][48][49][50][51][52][53] Most recently, some rap music has been characterized by the presence of explicit sexual language in its lyrics as well as messages of violence, racism, homophobia, and hatred toward women. 9,10,42,54 Drug, tobacco, and alcohol use also tend to be glorified in these songs.…”
Section: Introductionmentioning
confidence: 99%
“…Pero éstos han prestado poca atención tanto al por qué la gente se involucra en dichas escenas como al significado que dicha implicación añade a sus vidas. En su lugar, los expertos de la salud pública se han centrado en riesgos específicos como la conducción en estado de embriaguez [41][42][43] , el policonsumo de abuso 44,45 , la promiscuidad sexual y el riesgo de adquisición de VIH u otras enfermedades de transmisión sexual [46][47][48][49] , la gestión de la vida y los problemas interpersonales 38,[50][51] , las dependencias y adicciones 52 , y los problemas físicos y emocionales [53][54][55][56] . Los expertos de la salud pública también han examinado la escena hip hop.…”
Section: Research On Substance Use and Clubbingunclassified
“…40 Raves and modern electronic dance music clubbing have been especially targeted by public health researchers. Paying little attention to why people get involved with either or the meaning such involvement adds to their lives, public health scholars have focused, instead, on specific risks, such as driving while intoxicated [41][42][43] , poly-substance abuse [44][45] , sexual promiscuity and the risk of acquiring HIV and other sexually transmitted diseases [46][47][48][49] , life management and interpersonal problems 38,[50][51] , dependence and addiction 52 , and physical and emotional problems. [53][54][55][56] Public health scholars have also scrutinized hip hop scenes.…”
Section: Research On Substance Use and Clubbingmentioning
confidence: 99%